Fatal knowledges: the social and political legacies of collaboration and betrayal in Timor-Leste - Drexler, Elizabeth F. (International journal of transitional justice, 2013)
This article considers the case of Timor-Leste, occupied by Indonesia from 1975 to 1999, to elucidate the conditions that bedevil transitional justice processes in the aftermath of massive and long-running political violence, when a perpetrator state enjoys impunity because its wartime strategies facilitated denial of its responsibility, political violence was organized through the militarization of local society and individuals operated between the state and the resistance. The continuing social memory and knowledge of such conflict coupled with its judicial invisibility have significant consequences for rebuilding everyday lives. International agencies and processes have not only failed to attend to these dynamics in Timor-Leste but also replicated and perpetuated them, making the restoration of trust on which social reconstruction depends even more difficult.